Effect of functionalized gold nanoparticles on floating lipid bilayers - Tatur, Sabina; Maccarini, Marco; Barker, Robert; Nelson, Andrew; Fragneto, Giovanna (Langmuir, 2013)
The development of novel nano-engineered materials poses important questions regarding the impact of these new materials on living systems. Possible adverse effects must be assessed in order to prevent risks for health and the environment. On the other hand, a thorough understanding of their interaction with biological systems might also result in the creation of novel biomedical applications. We present a study on the interaction of model lipid membranes with gold nanoparticles (AuNP) of different surface modifications. Neutron reflectometry experiments on zwitterionic lipid double bilayers were performed in the presence of AuNP functionalized with cationic and anionic head groups. Structural information was obtained that provided insight into the fate of the AuNPs with regard to the integrity of the model cell membranes. The AuNPs functionalized with cationic head groups penetrate into the hydrophobic moiety of the lipid bilayers and cause membrane disruption at an increased concentration. In contrast, the AuNPs functionalized with anionic head groups do not enter but seem to impede the destruction of the lipid bilayer at an alkaline pH. The information obtained might influence the strategy for a better nanoparticle risk assessment based on a surface charge evaluation and contribute to nano-safety considerations during their design.
Gesehen am 31.01.2022